State, trust, and corporation - Maitland, Frederic William, 1850-1906 (Cambridge texts in the history of political thought., 2003)
Maitland's late, great essays on the historical origins of the state are collected in this volume. They contain a series of profound insights into the way the character of the state has been shaped by the non-political associations that exist alongside it - matters of continuing relevance today.